THE ROLE OF READING IN VOCABULARY EXPANSION AND LANGUAGE DEVELOPMENT (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2025)
Reading is a fundamental skill that plays a crucial role in vocabulary expansion and overall language development. It exposes learners to new words, sentence structures, and ideas, helping them improve their comprehension and communication skills. Whether reading for academic purposes, professional growth, or personal enjoyment, individuals benefit from increased linguistic knowledge. This article explores how reading contributes to vocabulary growth and language proficiency, emphasizing its importance in second-language acquisition.